2010
DOI: 10.1213/ane.0b013e3181d8cacf
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia and Analgesia Protocol During Therapeutic Hypothermia After Cardiac Arrest

Abstract: There is great variability in the protocols used for anesthesia and analgesia during therapeutic hypothermia. Very often, the drug and the dose used do not seem the most appropriate. Only 3 ICUs routinely used electroencephalographic monitoring during paralysis. It is necessary to reach a consensus on how to treat this critical care population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 65 publications
1
82
0
1
Order By: Relevance
“…Chamorro et al 26 found that fentanyl and morphine, in that order, were the most common analgesics used during therapeutic hypothermia after cardiac arrest. Both drugs effectively reduce shivering and cause moderate sedation; however, morphine has a greater risk of causing hypotension.…”
Section: Pharmacological Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chamorro et al 26 found that fentanyl and morphine, in that order, were the most common analgesics used during therapeutic hypothermia after cardiac arrest. Both drugs effectively reduce shivering and cause moderate sedation; however, morphine has a greater risk of causing hypotension.…”
Section: Pharmacological Methodsmentioning
confidence: 99%
“…Common sedatives used during therapeutic hypothermia to reduce the shivering threshold include propofol, dexmedetomidine, midazolam, and diazepam. Chamorro et al 26 conducted a systematic literature review and found that midazolam and propofol, in that order, were the sedative agents used most often. Doses of 2.5 to 10 mg of midazolam are moderately effective in reducing shivering, although the drug also has a high sedative effect and a low risk of hypotension.…”
Section: Pharmacological Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…98 Hypothermia decreases metabolism and excretion of midazolam in healthy individuals. 99 In addition, renal impairment is commonly encountered during the postarrest phase.…”
Section: Postcardiac Arrest Managementmentioning
confidence: 99%
“…However, caution is warranted during TH because peripheral nerve conduction is significantly slowed by cooling, and trainof-four testing may not be a reliable monitoring method at low body temperatures [70].…”
Section: Initiation Of Therapeutic Hypothermiamentioning
confidence: 99%